2009
DOI: 10.1007/s10711-009-9432-8
|View full text |Cite
|
Sign up to set email alerts
|

Insecurity for compact surfaces of positive genus

Abstract: A pair of points in a riemannian manifold $M$ is secure if the geodesics between the points can be blocked by a finite number of point obstacles; otherwise the pair of points is insecure. A manifold is secure if all pairs of points in $M$ are secure. A manifold is insecure if there exists an insecure point pair, and totally insecure if all point pairs are insecure. Compact, flat manifolds are secure. A standing conjecture says that these are the only secure, compact riemannian manifolds. We prove this for su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…The main result of this paper is the following: or P 2 (R), since totally insecure metrics for positive genus surfaces were already obtained in [3], as described in our introduction.…”
Section: Construction Of Totally Insecure Real Analytic Metrics On Smentioning
confidence: 95%
See 2 more Smart Citations
“…The main result of this paper is the following: or P 2 (R), since totally insecure metrics for positive genus surfaces were already obtained in [3], as described in our introduction.…”
Section: Construction Of Totally Insecure Real Analytic Metrics On Smentioning
confidence: 95%
“…The real analytic metrics h on S 2 for which we prove total insecurity are obtained in the same way as the metrics on S 2 for which K. Burns and Gerber [8,9] showed that the geodesic flow is ergodic. Our proof relies on ideas in [3] and techniques in non-uniform hyperbolicity [4,18]. Burns and Gutkin [6] and, independently, J.-F. Lafont and B. Schmidt [19] showed that compact Riemannian manifolds (of any dimension) with no conjugate points whose geodesic flows have positive topological entropy are totally insecure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were widely studied and applied in the literature, for example, [3], [4], [5], [6], [7], [10], [15], [18], [20], [31]. They were widely studied and applied in the literature, for example, [3], [4], [5], [6], [7], [10], [15], [18], [20], [31].…”
Section: Xiaojun Cuimentioning
confidence: 99%
“…V. Bangert and E. Gutkin obtained stronger results for the case when the dimension of M is two and the genus is positive [1]. They proved that if M has genus greater than one, then every Riemannian metric is totally insecure.…”
Section: Introductionmentioning
confidence: 99%